Phytochemical screening and investigation of in-vitro antioxidant and antibacterial activity of leea aequata leaf extract - Islam, Sabrina (BRAC University, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2017.